A low‐profile dual port UWB‐MIMO/diversity antenna with band rejection ability. Issue 1 (10th August 2017) - Biswal, Sonika Priyadarsini; Das, Sushrut
Abstract: A band notched ultra‐wideband (UWB) antenna is presented in this article as a good prospect for multiple‐input multiple‐output (MIMO)/diversity application. The proposed MIMO antenna is constituted of two modified rectangle‐shaped patch antenna elements. A stepped stub is extended from the modified ground plane as a decoupling element between the radiators to realize a good isolation level between them. A band rejection response is obtained by connecting an open resonant stub to each of the radiators. The simulated prototype is fabricated and tested for verification. Results reveal that the proposed prototype provides a 10 dB return loss bandwidth from 3.08 to 10.98 GHz with band notch characteristics from 4.98 to 5.96 GHz, and a good port isolation level ( S 21  ≤ 20). Diversity performances are ensured in terms of total active reflection coefficient, envelope correlation coefficient (<0.013 except notch band), diversity gain (≈9.51 dB), mean effective gain ratio (≈1), and channel capacity loss (≤0.35 bps/HZ except notch band). It evidences that the presented band notched UWB antenna can be a good prospective for MIMO/diversity applications.